Immunogenicity and safety of a live attenuated varicella vaccine in children aged 1 to 12 years: A double-blind, randomized, parallel-controlled phase III clinical trial in China - Shiyuan Wang; Yang Zhang; Guifan Li; Jinhui Shi; Xianyun Chang; Hao Zhang; Fengcai Zhu; Jingxin Li; Kai Chu; Jinfang Sun (Human Vaccines & Immunotherapeutics)
Chickenpox outbreaks frequently occur in collective settings such as kindergartens and schools, posing a significant threat to children’s physical and mental health. This study aimed to evaluate the immunogenicity and safety of the freeze-dried live attenuated varicella vaccine (VarV) developed by Beijing Minhai Biotechnology Co. LTD. in healthy participants aged 1–12 years. In this phase III, single-center, randomized, double-blind, active-controlled trial,1,200 healthy participants randomly assigned in a 1:1 ratio to receive one dose of either the test vaccine or the active control vaccine. Venous blood samples were collected before vaccination and 42 days after vaccination, and the fluorescent antibody to membrane antigen (FAMA) assay was used to detect VZV antibody. Adverse events (AEs) observed within 42 days after vaccination and serious adverse events (SAEs) within six months after vaccination were recorded. The seroconversion rates in the test and control groups were 96.79% and 96.43%, respectively, with a difference of 0.36% (95% CI, −1.76%–2.48%). The geometric mean titers (GMTs) were 61.74 and 58.04, respectively, with a difference of 1.06 (95% CI, 0.92–1.23). The lower limits of the 95% CI for the differences in seroconversion rates and GMT ratios between the two groups were greater than their respective pre-set non-inferiority margins. The overall incidence of AEs (p = .0112) in the test group was significantly lower than that in the control group. The freeze-dried live attenuated VarV developed by Beijing Minhai Biotechnology Co. LTD. demonstrated good immunogenicity and higher safety compared to the active control vaccine in healthy participants aged 1–12 years.